2012
DOI: 10.3759/tropics.21.21
|View full text |Cite
|
Sign up to set email alerts
|

Demographic costs of masting for a Bornean rain forest tree species, Scaphium macropodum

Abstract: Masting -the synchronous production of large fruit crops of conspecific trees among years -is a life history strategy in SE Asian tree species. While the reproductive biology of masting is relatively well described, the demographic consequences of masting are poorly understood. Theoretically, irregular production of seeds (masting) is less advantageous than annual fruiting for population growth, even if seed production is proportional to fruiting interval. This is related to the mortality risk between fruiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…This might be caused by the limited recruitment in the logged forest plots. A simulation study has shown slower recruitment for a lower relative abundance in small sized trees (Yamada et al 2012). We conclude that the observed reduced recruitment rate after selective logging will have little effect on the population growth rate but may result in large impacts on the population structure.…”
Section: Population Dynamicsmentioning
confidence: 94%
“…This might be caused by the limited recruitment in the logged forest plots. A simulation study has shown slower recruitment for a lower relative abundance in small sized trees (Yamada et al 2012). We conclude that the observed reduced recruitment rate after selective logging will have little effect on the population growth rate but may result in large impacts on the population structure.…”
Section: Population Dynamicsmentioning
confidence: 94%